Correlation Between Antioxidant and Cytotoxic Activity of Parijoto (Medinilla speciosa Blume) Fractions in 4T1 Cell Line - Annisaa', Eva; Sasikirana, Widyandani; Ekawati, Nuraini; Dini, Intan Rahmania Eka (Indonesian Journal of Cancer Chemoprevention, 2021)
Parijoto (Medinilla speciosa Blume) is one of Indonesian plant used for traditional medicine. Previous studies have demonstrated antimicrobial and cytotoxic effects of Parijoto on T47D cells. Therefore, we intended to know the antioxidant and cytotoxic activity of these fractions in 4T1 cell line (a Mus musculus mammary carcinoma). This cancer causes the greatest number of cancer-related deaths This study also investigated the correlation between antioxidant activity and cytotoxicity of Parijoto fractions. Discovering the type of correlation between antioxidant and anticancer activity of botanical extracts could relieve in screening for cytotoxic agent from natural products. The antioxidant and cytotoxic activity investigated using the Diphenylpicrylhydrazyl (DPPH) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay methods. The result showed that ethyl acetate fraction is the higher antioxidant activity (IC50:1.77 μg/mL) and the higher cytotoxicity (IC50:133.57 μg/mL). There was a strong positive correlation (correlation coefficient=0.957) between antioxidant and cytotoxic activity in 4T1 cell line, but the correlation was not significant (p=0.188).Keywords: Parijoto (Medinilla speciosa Blume), antioxidant, cytotoxic, 4T1 cell line.